Bribery-export nexus under the firm's growth obstacles - Trang Hoai Phan; Rainer Stachuletz (Economies, 2022)
Business bribery is a particularly serious problem in the integration era. First, this article investigates the effects of institutional obstacles on firms' bribery in 131 countries classified by nation income groups. Through the appropriate proposal of fitting functions, the relationship between obstructions and the predicted margin effect of bribery is intuitively elucidated. Second, this paper sheds light on the relationship between bribery payment and exports. Then the analysis is upgraded when controlling for the moderation of a firm's growth constraints. The results detected that not only institutional barriers, but also internal and external hindrances play an essential role in the interaction between bribe payments and export share. More interestingly, this study scrutinizes the role of obstacles in this relationship separately. Besides, SMEs and large enterprises are also adopted in further sensitivity analyses. To solve the endogeneity problem, the study uses the average amount of bribery in a firm's location, sector, and the country as an instrumental variable (IV). The results obtained are not consistent across country groups classified by national income. Due to obstacles during a firm's operation, the amplitude of the positive effect of bribery on exports is reduced.
Keywords: 330; bribery; export; firm's growth obstacles; instrumental variable; National Income Classification; probit regression